Elevated transaminases potentiate the risk for emerging dysglycemia in children with overweight and obesity. Issue 12 (21st June 2021) - Koutny, Florian; Stein, Robert; Kiess, Wieland; Weghuber, Daniel; Körner, Antje
Summary: Background: There is evidence that nonalcoholic fatty liver disease (NAFLD) increases the risk for dysglycemia in children in cross‐sectional studies. However, the extent to which NAFLD may confer the risk for dysglycemia in longitudinal studies remains uncertain. Objectives: We investigated whether elevated levels of alanine aminotransferase (ALT) as a proxy for NAFLD can serve as a predictor for future dysglycemia among children. Methods: We performed survival analysis up to 11 years of follow‐up on longitudinal data of 510 children with overweight and obesity from the Leipzig Childhood Cohort. Results: Children with overweight/obesity and elevated ALT values had a more than 2‐fold increased risk (hazard ratio 2.59, 95% confidence interval 1.49 to 4.50; P < 0.01) for future dysglycemia independent of age, sex and BMI‐SDS. Conclusions: Elevated transaminases are an early predictor for glycemic deterioration. Hence, NAFLD should further be addressed as a risk factor and therapeutic target for the early prevention of type 2 diabetes.